Mathematics in the Tordauk jerpara tel tradition: Contribution of local wisdom to mathematics education innovation in elementary schools - Labuem, Susana; Sa'dijah, Cholis; Parta, I Nengah; Sulandra, I Made (Journal on Mathematics Education, 2025)
This research aimed to present a unique approach by integrating the Tordauk jerpara tel tradition of the Aru community into formal mathematics learning, describing the relationship between local cultural practices and mathematics concepts. The objectives were to identify the mathematics values contained in tradition and design a strategy for integrating the values into the elementary school curriculum to improve conceptual understanding and global mathematics literacy. A qualitative approach with an ethnomathematics design was adopted, additionally 20 third-grade elementary school students in Aru Regency were selected as participants. Data were collected through observation, role playing, interviews, and document analysis. The results showed the Tordauk jerpara tel tradition contained the concepts of addition, subtraction, multiplication, division, fractions, decimals, ratios, averages, and modulo arithmetic, which could be systematically mapped into the formal elementary school mathematics. The five-stage learning strategy, namely contextual exploration, mathematics identification, formalization, contextual reflection, and extension, can increased student engagement, abstraction ability, thinking flexibility, and internalization of social values. This research made theoretical contributions to ethnomathematics and culture-based mathematics education, while also proposing an adaptable strategy implemented in international contexts. Practical implications include the development of contextual with further research directions focused on strategy validation across cultural contexts.